Removal of nutrients, organic matter, and metal from domestic secondary effluent through microalgae cultivation in a membrane photobioreactor. Issue 10 (2nd February 2016) - Gao, Feng; Li, Chen; Yang, Zhao‐Hui; Zeng, Guang‐Ming; Mu, Jun; Liu, Mei; Cui, Wei
Abstract: Background: Microalgae cultivation has been suggested as a prospective method for advanced wastewater treatment. This study investigated the removal of nitrogen, phosphorus, organic matter, and metal ions from domestic secondary effluent using a membrane photobioreactor (MPBR), in which Chlorella vulgaris was cultured in a continuous flow mode. The filtration effect of the membrane module submerged in the reactor prevented the microalgae cells from being washed out and enabled the reactor to operate at a high supply rate. Results: The MPBR achieved highly efficient microalgae production in diluted wastewater. The maximum growth biomass of microalgae in the MPBR supplied with secondary effluent was 1.724 g L −1, which was 1.64 times higher than that grown in a conventional photobioreactor (CPBR) with BG11 medium. The rapid growth of microalgae in the reactor also benefited the removal of contaminants, such as nutrients. The average treatment performances of the MPBR were found to be 87.7% for nitrogen and 76.7% for phosphorus in the stable stage. Metal ions such as Cu, Zn, Fe, Al, and Mn in the secondary effluent were also efficiently removed. Conclusions: Highly efficient microalgae production and high quality effluent in terms of nutrients and metal ions were simultaneously achieved in the MPBR. © 2016 Society of Chemical Industry